(2 1/6-1/3)*2 2/5=?
2 2/7*7-(3 1/2) do potęgi 2 =?
(2 1/2-1 1/3) do potęgi 2 - (5/6) do potęgi 2 =?
(1 1/2) do potęgi 3 * (2/3) do potęgi 3 - 1/5*2 1/6= ?
Proszę was o najszybszą odpowiedź .


Odpowiedź :

Odpowiedź:

a=4,4

b=3,75

c=0.66666666666

d=0.56666666666

Szczegółowe wyjaśnienie:

mam nadzieje że pomoge

Odpowiedź:

(2 1/6 - 1/3) * 2 2/5 = (1 7/6 - 2/6) * 12/5 = 1 5/6 * 12/5 = 11/6 * 1/5 = 11/30

2 2/7 * 7 - (3 1/2)² = 16/7 * 7 - (7/2)² = 16 - 49/4 = 16 - 12 1/4 = 3 3/4

(2 1/2 - 1 1/3)² - (5/6)² = (2 3/6 - 1 2/6)² - 25/36 = (1 1/6)² - 25/36 = (7/6)² - 25/36 =

= 49/36 - 25/36 = 24/36 = 2/3

(1 1/2)³ * (2/3)³ - 1/5 * 2 1/6 = (3/2)³ * 8/27 - 1/5 * 13/6 = 27/8 * 8/27 - 13/30 =

= 1 - 13/30 = 17/30

Szczegółowe wyjaśnienie: